Comparison of B+1 and SAR efficiency for a high-impedance metamaterial shield with different remote RF arrays at 7 T MRI: a simulation study - López-Martínez, Ignacio N.; Ladd, Mark E.; Schmidt, Rita; Orzada, Stephan (Magnetic resonance materials in physics, biology and medicine, 2025)
This study explores high-impedance surface (HIS) metamaterial shields for enhancing the transmit field in whole-body MRI at 7 T. We studied the possibility of placing a metamaterial layer between the gradient coil and bore liner using electromagnetic simulations to evaluate B1+ and SAR efficiency across different impedances.